2022
DOI: 10.1002/advs.202201875
|View full text |Cite
|
Sign up to set email alerts
|

Exciton Transfer at Heterointerfaces of MoS2 Monolayers and Fluorescent Molecular Aggregates

Abstract: Integration of distinct materials to form heterostructures enables the proposal of new functional devices based on emergent physical phenomena beyond the properties of the constituent materials. The optical responses and electrical transport characteristics of heterostructures depend on the charge and exciton transfer (CT and ET) at the interfaces, determined by the interfacial energy level alignment. In this work, heterostructures consisting of aggregates of fluorescent molecules (DY1) and 2D semiconductor Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This is in line with the strong RSA caused by electron transfer from ZnO to V Re -ReS 2 of DL mentioned earlier. 14 In addition, the Re vacancy causes the formation of DL, which can lead to more efficient interfacial CT, so the formation of the Zn–S bond is once again proven. 50…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with the strong RSA caused by electron transfer from ZnO to V Re -ReS 2 of DL mentioned earlier. 14 In addition, the Re vacancy causes the formation of DL, which can lead to more efficient interfacial CT, so the formation of the Zn–S bond is once again proven. 50…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to exciton transfer via band filling. 14 Carrier lifetimes of V Re -ReS 2 and V Re -ReS 2 @ZnO were fitted using double exponential functions, as shown in Table S1 (ESI †). Carrier lifetime of V Re -ReS 2 : t 1 = 1.89 ps, t 2 = 2.6 ps, t 3 = 2.2 Â 10 3 ps.…”
Section: Nonlinear Optical and Transient Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal changes in the light-induced contact potential difference (CPD) at the DY1/MoS 2 interface eliminated the possibility of an interlayer charge transfer process, confirming the formation of a type-I heterojunction. 30 Again, it is found that while the excited-state electron transfer rate from TMDs (MoS 2 and WSe 2 ) to fullerenes (C 60 ) is relatively insensitive due to the band offset (more details discussed earlier), the electron transfer (ET) rate from TMDs to PTCDA is reduced by an order of magnitude when the band offset is quite large. 140 For the perylene crystal, the sensitivity of the electron transfer rate on the band offset is elucidated by the 1D nature of the electronic wave function, which limits the availability of states with the appropriate energy to accept the electron.…”
Section: Strong Optical Response In Tmdomentioning
confidence: 94%
“…This observation points to a robust electronic interaction between these two materials. 30 In type II, in particular p–n junction, TMDO heterostructures, generally the PL emission peak quenches for individual layers; however, recently an extra ILX emission peak from the NIR to IR range has been observed. Due to their spatially indirect nature, interlayer excitons possess long-lifetimes, attributed to the reduced overlap between electron and hole wavefunctions, 31,32 extended spatial coherence of the excitons, 33 quantum emitter, 34 and high-temperature exciton condensate.…”
Section: Introductionmentioning
confidence: 99%